Cost of stroke from patients' perspective: A real-world evidence study in Vietnam - Nga, Nguyen Thi To; Thanh, Le Thi Ngoc; Thang, Nguyen Huy; Man, Tieu Tu; Son, Pham Luong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Introduction: Stroke is the second leading cause of death worldwide, accounting for 10% of all deaths and 17 million new cases annually. Its impact on society is enormous, not only due to the disease burden but also because of the associated medical costs. Studies on the cost of stroke in Vietnam have been limited so far. The aim of this study is to evaluate stroke-related costs from the patients' perspective in Vietnam using hospital data. Methods: A cross-sectional study using a randomized sample of stroke patients from a hospital in Ho Chi Minh City (115-bed hospital) was conducted to evaluate the cost of stroke. Patients who were hospitalized for stroke at the studied hospital, had complete medical records, and agreed to participate in the study were selected. Patients who were foreigners, did not complete their treatment at the research hospital, or died during treatment were excluded from the study. The costs of stroke considered both direct (medical and nonmedical) and indirect expenses. Results: Based on the study sample of 273 patients with ratio of men: women of 1.315:1, mean age of 62.97± 14.3; approximately 85% with ischemic stroke and 15% with hemorrhagic stroke. The mean total cost per stroke patient was VND 8,112,458.7 ± 285.499,16; 77% of which was due to direct cost (VND 6,307,554.5) and the rest (23%) was due to indirect cost (VND 1,804,904.2). In the structure of direct cost, the medical costs were 1,22 times higher than non-medical costs (3,470,583.8 vs 2,836,970.7 VND; respectively). Discussions: This study was conducted on a small scale, involving only one hospital and a limited study period, which led to constraints in sample size. The study demonstrated the treatment costs for stroke inpatients and highlighted the variations in different types of stroke-related expenses. These findings can assist medical centers and physicians in making informed clinical decisions. Additionally, the results provide a basis for shaping policy decisions and developing national medical programs. Conclusions: With an average hospital stay of 6.17 ± 0.18 days, direct medical costs constituted the largest portion of the total expenses. Given the increasing incidence of stroke in Vietnam, healthcare policies aimed at reducing the financial burden on stroke patients should be considered.